Efficient Hierarchical Identity-Based Signature With Batch Verification for Automatic Dependent Surveillance-Broadcast System - Debiao He; Kumar, Neeraj; Choo, Kim-Kwang Raymond; Wei Wu (IEEE transactions on information forensics and security, 2017)
The automatic-dependent surveillance-broad-cast (ADS-B) is generally regarded as the most important module in air traffic surveillance technology. To obtain better airline security, ADS-B system will be deployed in most airspace by 2020, where aircraft will be equipped with an ADS-B device that periodically broadcasts messages to other aircraft and ground station controllers. Due to the open communication environment, the ADS-B system is subject to a broad range of attacks. To simultaneously implement both integrity and authenticity of messages transmitted in the ADS-B system, Yang et al. proposed a new authentication frame based on the three-level hierarchical identity-based signature (TLHIBS) scheme with batch verification, as well as constructing two schemes for the ADS-B system. However, neither TLHIBS schemes are sufficiently lightweight for practical deployment due to the need for complex hash-to-point operation or expensive certification management. In this paper, we construct an efficient TLHIBS scheme with batch verification for the ADS-B system. Our scheme does not require hash-to-point operation or (expensive) certification management. We then prove the TLHIBS scheme secure in the random oracle model. We also demonstrate the practicality of the scheme using experiments, whose findings indicate that the TLHIBS scheme supports attributes required by the ADS-B system without the computation cost in Chow et al.'s scheme and Yang et al.'s TLHIBS schemes.